Expert judgments about transient climate response to alternative future trajectories of radiative forcing - Zickfeld, Kirsten (National Academy of Sciences, 2010)
There is uncertainty about the response of the climate system to future trajectories of radiative forcing. To quantify this uncertainty we conducted face-to-face interviews with 14 leading climate scientists, using formal methods of expert elicitation. We structured the interviews around three scenarios of radiative forcing stabilizing at different levels. All experts ranked “cloud radiative feedbacks” as contributing most to their uncertainty about future global mean temperature change, irrespective of the specified level of radiative forcing. The experts disagreed about the relative contribution of other physical processes to their uncertainty about future temperature change. For a forcing trajectory that stabilized at 7 Wm(-2) in 2200, 13 of the 14 experts judged the probability that the climate system would undergo, or be irrevocably committed to, a “basic state change” as ≥0.5. The width and median values of the probability distributions elicited from the different experts for future global mean temperature change under the specified forcing trajectories vary considerably. Even for a moderate increase in forcing by the year 2050, the medians of the elicited distributions of temperature change relative to 2000 range from 0.8–1.8 °C, and some of the interquartile ranges do not overlap. Ten of the 14 experts estimated that the probability that equilibrium climate sensitivity exceeds 4.5 °C is > 0.17, our interpretation of the upper limit of the “likely” range given by the Intergovernmental Panel on Climate Change. Finally, most experts anticipated that over the next 20 years research will be able to achieve only modest reductions in their degree of uncertainty.